Nurse practitioner Bi-level clinics for patients with morbid obesity. Issue 2 (1st June 2012) - Hart, D
Abstract : Obesity is a substantial public-health crisis in the developed world. The prevalence is increasing rapidly in numerous developing nations worldwide. This growing rate represents a pandemic that needs urgent attention if its potential morbidity, mortality, and economic tolls are to be avoided. Morbid obesity is a serious health condition that can interfere with basic physical functions such as breathing or walking. . Those who are morbidly obese are at greater risk for illnesses including diabetes, high blood pressure, sleep apnoea, gastro oesophageal reflux disease gallstones, osteoarthritis, heart disease, and cancer. Although the exact magnitude of the attributable excess in mortality associated with obesity (112, 000-365, 000 excess deaths annually) has been disputed, obesity is indisputably the greatest preventable health-related cause of mortality after cigarette smoking. The Bi-level clinics were started for patients who required constant nocturnal Non Invasive Ventilation (NIV) at home for morbid obesity. Their care is delivered by the Respiratory Nurse Practitioner with back up from other members of the respiratory team as required All the patients with obesity seen in the clinic have very high BMI's ranging from 44-92.They are all at significant risk of dying from multiple co- morbidities. The Nurse practitioner has taken the responsibility to have and document end of life discussions with these patients following the death of one patient that turned into a media frenzy. It divided many people in New Zealand who had not understood the major underlying problem for the death. The aim of the Bi-level clinics is to provide specialised expert care to this vulnerable group of patients who have multiple medical and social issues. As a Nurse practitioner with many years of experience with the variety of ethnicities in the hospital catchment I feel I can offer a quality service for these patients many of whom have now avoided hospital admission for several years.